2009
DOI: 10.1038/jp.2009.139
|View full text |Cite
|
Sign up to set email alerts
|

School-age outcomes of newborns treated for persistent pulmonary hypertension

Abstract: Objective: The aim of this study was to describe the school-age outcome of a cohort of children treated with intensive care support for persistent pulmonary hypertension of the newborn (PPHN).Study Design: From 187 term newborns treated for PPHN as neonates, 109 were seen at school age (73% of 150 survivors and 58.2% of the original cohort). Of these 109 term newborns, 77 were treated with inhaled nitric oxide (iNO); of which 12 received extracorporeal membrane oxygenation (ECMO). The remaining 32 received con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Rosenberg et al investigated school age outcomes of infants treated with iNO for PPHN and did not find an association between iNO and adverse neurodevelopmental outcome. [36] Interestingly, though, a trend towards poorer outcome in children with CDH treated with iNO was noted, with a 33% rate of moderate or severe handicap in this subgroup.…”
Section: Discussionmentioning
confidence: 92%
“…Rosenberg et al investigated school age outcomes of infants treated with iNO for PPHN and did not find an association between iNO and adverse neurodevelopmental outcome. [36] Interestingly, though, a trend towards poorer outcome in children with CDH treated with iNO was noted, with a 33% rate of moderate or severe handicap in this subgroup.…”
Section: Discussionmentioning
confidence: 92%
“…It was used to examine the effect of different exposures including health conditions like traumatic injuries (Moore, Donders & Thompson, 2004; Donders & Nesbit-Greene, 2004; Horneman & Emanuelson, 2009), brain dysfunction (Allen, Knatz & Mayfield, 2006; Bello, Allen & Mayfield, 2008), diseases (Rosenberg et al, 2010), marihuana and cocaine (Fried, Watkinson & Gray, 2005; Ga et al, 2015), disabilities (Hinton et al, 2004), chemical products (Debes et al, 2006; Wright et al, 2006; Jurewicz, Polańska & Hanke, 2013), and alcohol (Mattson et al, 1998). CCT-1 is an individually administered standardized test for children from 5 to 8 years to test their ability to solve problems on the basis of corrective feedback.…”
Section: Methodsmentioning
confidence: 99%
“…The rate of neurodevelopmental disabilities including cognitive delays and hearing deficit can be seen in 6.4% of PPHN survivors (42). Feeding problems and short term respiratory morbidities can be seen also in 24% of PPHN survivors (42).…”
Section: Outcomementioning
confidence: 99%
“…The rate of neurodevelopmental disabilities including cognitive delays and hearing deficit can be seen in 6.4% of PPHN survivors (42). Feeding problems and short term respiratory morbidities can be seen also in 24% of PPHN survivors (42). Rosenberg et al found no differences in medical, neurodevelopmental, and social/emotional/behavioral outcomes at school age, between children with PPHN who were treated with iNO, with or without ECMO, and infants who were treated without exposure to iNO (42).…”
Section: Outcomementioning
confidence: 99%
See 1 more Smart Citation